Application of Peroxide Curing Systems in Cross-Linking of Rubber Magnets Based on NBR and Barium Ferrite - Ján Kruželák; Andrea Kvasničáková; Elena Medlenová; Rastislav Dosoudil; Ivan Hudec (Advances in Materials Science and Engineering)
Rubber magnetic composites were prepared by incorporation of barium ferrite in constant amount—50 phr into acrylonitrile-butadiene rubber. Dicumyl peroxide as the curing agent was used for cross-linking of rubber magnets alone, or in combination with four different types of co-agents. The main aim was to examine the influence of curing system composition on magnetic and physical-mechanical properties of composites. The cross-link density and the structure of the formed cross-links were investigated too. The results demonstrated that the type and amount of the co-agent had significant influence on cross-link density, which was reflected in typical change of physical-mechanical properties. The tensile strength increased with increasing amount of co-agents, which can be attributed to the improvement of adhesion and compatibility on the interphase filler-rubber due to the presence of co-agents. Magnetic characteristics were found not to be influenced by the curing system composition. The application of peroxide curing systems consisting of organic peroxide and co-agents leads to the preparation of rubber magnets with not only good magnetic properties but also with improved physical-mechanical properties, which could broaden the sphere of their application uses.